Development of Strabismus in Children Initially Diagnosed with Pseudostrabismus. (2nd April 2016) - Sefi-Yurdakul, Nazife; Tuğcu, Betül
ABSTRACT: Purpose : To evaluate the incidence of strabismus in children initially diagnosed with pseudostrabismus and to identify risk factors for the development of strabismus. Methods : The medical records of patients who were diagnosed with pseudostrabismus at initial examinations in outpatient clinic were reviewed retrospectively. Follow-up examinations were made at the strabismus department. Age at first examination, gender, family and developmental history, ophthalmic and orthoptic findings including orbit, and eyelid pathologies were investigated. Results : Sixty-five patients with the diagnosis of pseudostrabismus were identified; 2 patients (3.1%) had pseudoexotropia, and 63 patients (96.9%) had pseudoesotropia. The mean age at the initial exam was 29.26±26.68 months (range; 4–120 months). Epicanthal skin folds (n=35), flat broad nasal bridge (n=17), blepharophimosis syndrome (n=1), hypertelorism (n=1), telecanthus (n=1), and multiple pathologies (n=10) were the reasons for pseudostrabismus. Six patients (9.2%) had clinically significant hypermetropia. Anisometropia and amblyopia were detected in 1 (1.5%) and 3 patients (4.6%), respectively, at the initial examination. The mean follow-up period was 25.2±23.28 months (range; 1–154 months). During the follow-up period, true strabismus was detected in 8 cases (12%); of these, 5 cases had non-refractive esotropia, 2 cases had refractive accommodative esotropia, and 1 case had exotropia. Binocular single vision was not developed following amblyopia therapy and refractive correction in esotropic cases. Binocular single vision and best corrected visual acuity were statistically significant risk factors for the development of strabismus ( P =0.001). Conclusion : The pseudostrabismic children with subnormal binocular single vision or low visual acuity require follow-up for the risk of development of true strabismus.